2018
DOI: 10.1080/14686996.2018.1433439
|View full text |Cite
|
Sign up to set email alerts
|

Material challenges for solar cells in the twenty-first century: directions in emerging technologies

Abstract: Photovoltaic generation has stepped up within the last decade from outsider status to one of the important contributors of the ongoing energy transition, with about 1.7% of world electricity provided by solar cells. Progress in materials and production processes has played an important part in this development. Yet, there are many challenges before photovoltaics could provide clean, abundant, and cheap energy. Here, we review this research direction, with a focus on the results obtained within a Japan–French c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(100 citation statements)
references
References 289 publications
(218 reference statements)
1
99
0
Order By: Relevance
“…Optical measurements based on photoluminescence (PL) allow for a fast screening. A widely used criterion for the suitability of a (new) material for solar cell applications is the radiative efficiency or the quasi Fermi level (qFL) splitting. Both quantities are closely related .…”
Section: Introductionmentioning
confidence: 99%
“…Optical measurements based on photoluminescence (PL) allow for a fast screening. A widely used criterion for the suitability of a (new) material for solar cell applications is the radiative efficiency or the quasi Fermi level (qFL) splitting. Both quantities are closely related .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show very promising results from perovskite materials which have rather slow carrier energy relaxation and thus can provide better opportunities to achieve higher carrier temperatures, though the exact physical mechanism responsible for these phenomena is not fully understood yet. In short, the possibilities and potentials of hot‐carrier solar cells are still waiting to be explored and exploited …”
Section: Resultsmentioning
confidence: 99%
“…However, a recent theoretical study has suggested that carrier temperatures can be significantly higher than the lattice temperatures in conventional solar cells, especially when photovoltaic devices operate near a short-circuit condition. 14 On the contrary, for hot-carrier solar cells [15][16][17][18][19][20][21][22][23][24] in which the kinetic energy of carriers is extracted to become output electrical power, the carrier temperature becomes the main focus [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ; hence, intraband carrier-carrier scattering is crucial and cannot be ignored.…”
mentioning
confidence: 99%
“…Most scientists in the field of photovoltaics agree that there are two directions for improving this field of research. One direction is related to research of solar cell materials and design of photovoltaic (PV) devices in order to achieve a cheap product, much cheaper than today's most used the silicon solar cells . Because of the still high cost of currently used solar PV systems, this direction could be named as a low‐cost approach.…”
Section: Introductionmentioning
confidence: 99%
“…One direction is related to research of solar cell materials and design of photovoltaic (PV) devices in order to achieve a cheap product, much cheaper than today's most used the silicon solar cells. [1][2][3] Because of the still high cost of currently used solar PV systems, this direction could be named as a low-cost approach. On the other hand, we have to find a way to use today's designed PV devices in a better way in the sense that we can reduce NOMENCLATURE: I 0 , the initial light source intensity; I sc , the short circuit current; IXYS KXOB22, monocrystalline Si solar cell; J sc , the short circuit current density; Osram 120V GY5.3ELH, Halogen lamp; P input , the input light energy; PV, photovoltaic; STC, Standard Test Condition; ULTRA-VITALUX 300-280 E27, Tunsten lamp; V oc , the open circuit voltage; WFL system, the water flow lens system; 1 Sun, 1000W/m 2 the production costs of electricity.…”
Section: Introductionmentioning
confidence: 99%